1-(Dicyanomethylene)-3-hydroxy-1H-indene-2-carboxylic Acid - Sofia D. Usova; Ekaterina A. Knyazeva; Oleg A. Rakitin (Molbank)
Bulk heterojunction solar cells are among the most promising organic solar cells (OSCs). One of the two important parts of OSCs are acceptors, and the development of the design and synthesis of non-fullerene acceptors involves an electron-deficient heterocyclic central core and anchor acceptor malonitrile derivatives of 3-methylene-2,3-dihydro-1H-inden-1-ones. In this communication, an intermediate for the synthesis of this compound, 1-(dicyanomethylene)-3-hydroxy-1H-indene-2-carboxylic acid, was prepared by the Perkin reaction of 2-(3-oxoisobenzofuran-1(3H)-ylidene)malononitrile with tert-butyl acetoacetate in the presence of acetic anhydride and triethylamine. The structure of the newly synthesized compound was established by means of elemental analysis, high-resolution mass spectrometry, 1H NMR, 13C NMR and IR spectroscopy, and mass spectrometry.